2011
DOI: 10.1002/elps.201100321
|View full text |Cite
|
Sign up to set email alerts
|

The challenge to quantify proteins with charge trains due to isoforms or conformers

Abstract: Single proteins separated by 2-DE often show multiple spots spreading along the first dimension. In many cases, such charge trains are explained by isoform differences or by putative post-translational modifications including phosphorylation, glycosylation and others. We now report that individual spots of such charge trains on 2-D gels in fact often represent the same protein, but, apparently due to conformational changes, segregate to different isoelectric points. If MS analysis reveals protein identity, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…As there are three Glo-3 genes in the wheat cultivar Glenlea [15], it is feasible that AC Barrie would also have three Glo-3 genes, as both AC Barrie and Glenlea are closely related hexaploid wheat cultivars [32]. The charge trains of gel spots with similar M r and a range of pI values at the major size groups (Figure 2) are likely due to post-translational processing and modifications, as previously discussed [17], as well as amino acid substitutions between the multiple immunologically related Glo-3 proteins in AC Barrie, or from artifacts generated during the execution of the extraction and examination protocols [33]. …”
Section: Discussionmentioning
confidence: 94%
“…As there are three Glo-3 genes in the wheat cultivar Glenlea [15], it is feasible that AC Barrie would also have three Glo-3 genes, as both AC Barrie and Glenlea are closely related hexaploid wheat cultivars [32]. The charge trains of gel spots with similar M r and a range of pI values at the major size groups (Figure 2) are likely due to post-translational processing and modifications, as previously discussed [17], as well as amino acid substitutions between the multiple immunologically related Glo-3 proteins in AC Barrie, or from artifacts generated during the execution of the extraction and examination protocols [33]. …”
Section: Discussionmentioning
confidence: 94%
“…Hulse described the interbatch variability of the amount of dimers in BSA . Deng and Hahne showed that BSA is able to form seven isoforms, which were specified as “transient conformers,” with slightly different pIs in the range from 5.5 to 5.8 but approximately the same size . The shoulder at 7.2 min in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…). In addition to the reduction of the peak areas, one of the two species of BSA , which are separated, seemed to undergo a structural rearrangement. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the used MALDI MS peptide mapping analysis in combination with evaluation of the isotope distribution profiles does not allow the detection of deamidation if only a very small proportion of a peptide is modified. Clearly, deamidation contributes substantially—together with other charge‐affecting PTMs and possibly experimentally caused modifications —to heterogeneous populations of protein forms, which then separate into spots with nearly identical p I values.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is evidence that charge trains in 2DE may also be caused by conformational changes, e.g. or experimental artifacts .…”
Section: Introductionmentioning
confidence: 99%